Characteristics of Student Metacognition in Mathematical Problem Solving Viewed From Personality Types - Agustin, Dina; Edy, Sarwo; Huda, Syaiful (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2023)
The ability to solve a problem is one of the main aspects of learning mathematics in schools, starting from elementary school to high school. Many factors need to be considered in solving mathematical problems, one of which is metacognition and personality type. The purpose of this research is to describe the metacognitive characteristics of students in solving mathematical problems in terms of personality type. Data collection methods that researchers use are questionnaire methods, test methods, and interview methods. The results show that, students with high levels of metacognitive ability are able to identify what is known and what is asked, are able to think of action plans, are able to build alternative solutions, and feel they do not need to check again when they are finished working, students with moderate metacognitive abilities able to identify what is known and what is asked, able to think of action plans, able to build alternative solutions, and feel the need to re-check the answers that have been made, students with low-level metacognitive abilities are not able to identify what is known and what is being asked, not able to think of an action plan, unable to develop alternative solutions, and feel no need to check again when finished working.